Sex, culture, and justice : the limits of choice - Chambers, Clare, 1976- (Pennsylvania State University Press, 2008)
Autonomy is fundamental to liberalism. But autonomous individuals often choose to do things that harm themselves or undermine their equality. In particular, women often choose to participate in practices of sexual inequality-cosmetic surgery, gendered patterns of work and childcare, makeup, restrictive clothing, or the sexual subordination required by membership in certain religious groups. In this book, Clare Chambers argues that this predicament poses a fundamental challenge to many existing liberal and multicultural theories that dominate contemporary political philosophy. Chambers argues that a theory of justice cannot ignore the influence of culture and the role it plays in shaping choices. If cultures shape choices, it is problematic to use those choices as the measure of the justice of the culture. Drawing upon feminist critiques of gender inequality and poststructuralist theories of social construction, she argues that we should accept some of the multicultural claims about the importance of culture in shaping our actions and identities, but that we should reach the opposite normative conclusion to that of multiculturalists and many liberals. Rather than using the idea of social construction to justify cultural respect or protection, we should use it to ground a critical stance toward cultural norms. The book presents radical proposals for state action to promote sexual and cultural justice.